A Consumer Acceptance Study of An Electronic Dinar Payment System - Mohd Nazri Muhayiddin; Elsadiq M.A.; Paul H.P. Yeow (2011)
The aim of this study is find solutions to a few limitations naturally associated with physical dinar coins. Specifically this research proposes the use of a dinar based electronic payment system. But before actual system can be implemented, this research is intended to find out whether the public would be ready to adopt the proposed electronic dinar payment system. The research framework for this study will be based on Unified Theory of Acceptance and Use of Technology (UTAUT) (Venkatesh et al., 2003). It will measure user acceptance based on these constructs i.e. the Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Behavioral Intention to Use, and with two new variables added: Anxiety, and Perceived Credibility. Data collection is based on questionnaire surveys. This preliminary study discovered that most of the respondents participated in this survey generally agree with the idea of using the proposed electronic dinar payment system